Molecular and Immobilized Tripodal Phosphine Ligands and Their Trinuclear Palladium Complexes - Maxwell R. Kimball; Kyle J. Cluff; Nattamai Bhuvanesh; Janet Blümel (Molecules)
The synthesis and characterization of the tripodal phosphines RSi(CH2CH2PPh2)3 (R = Me, OMe, OEt) (1–3) is described. The 1H NMR spectra of all phosphines display virtual coupling patterns. The ligands form the corresponding trinuclear Pd complexes [RSi(CH2CH2PPh2)3]2(PdCl2)3 (4–6) with three PdCl2 moieties sandwiched between two tripodal ligands. The complexes 4, 5, and 7 (R = OH) have been analyzed by single crystal X-ray diffraction. The coordination at the Pd center is square planar with the phosphine groups occupying trans positions. The 31P{1H} MAS NMR spectra of polycrystalline 1 are in accordance with the packing motif of the molecules in the unit cell. The tripodal ligand 3 has successfully been immobilized on silica as 3i. It coordinates PdCl2 on the surface, as demonstrated by 31P{1H} MAS NMR. Hereby, the cis coordination is prevalent when 3i has maximal surface coverage. At low surface coverage, one tripodal linker can accommodate trans coordination at the metal center. A surface-bound trinuclear Pd complex has been generated, as well as a heterobimetallic Pd/Cu complex. All surface species have been characterized by 31P{1H} MAS NMR.